Including local voices in marine debris conversations to advance environmental justice for island and coastal communities: perspectives from St. Paul Island, Alaska - Veronica M. Padula; Anne H. Beaudreau; Douglas Causey; Lauren M. Divine; Marissa Merculieff (FACETS, 2023)
Marine debris is ubiquitous across the global ocean and is an increasing threat to human health, economies, habitats, and wildlife. While local to national action plans are important in addressing this issue, they do not necessarily reflect the needs of coastal communities most heavily impacted. Remote island and coastal communities, particularly in Alaska, do not generate the majority of marine debris impacting their ecosystems; however, they are often left with the task of removal and disposal. Thus, the detrimental effects of marine debris are not only an ecological problem but an issue of environmental justice. This project aimed to catalyze the inclusion of place-based knowledge in marine debris solutions for St. Paul Island, a predominantly (>85%) Alaska Native community in the Bering Sea. We interviewed 36 community members during 2017–2020, documenting their observations of marine debris types, amount, distribution, and impacts over recent decades. Participants reported increasing plastic debris since the 1980s, particularly plastic bottles and fishing gear. Nearly 80% expressed concern about impacts to subsistence resources, including entanglement and ingestion. St. Paul Island community members’ experiences highlight that solving marine debris issues requires broader policies and mitigation strategies addressing sources of debris and advancing environmental justice by impact reduction. Furthermore, this case study can serve as an example of how locally relevant action plans can be developed in other coastal communities around the world by including knowledge and concerns of community members, as they are the most heavily and personally impacted by the marine debris on their shorelines.